1998
DOI: 10.1007/s11746-998-0126-4
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative activity of green tea catechin extract compared with that of rosemary extract

Abstract: This study compared the antioxidative activity of green tea catechin (GTC) extract with that of rosemary extract in canola oil, pork lard, and chicken fat. The GTC extract was obtained from jasmine and longjing green teas and mainly consisted of four epicatechin isomers including (−)epigallocatechin gallate (EGCG), (−)epigallocatechin (EGC), (−)epicatechin (EC), and (−)epicatechin gallate (ECG). The oxidation was conducted at 100 ± 2°C by monitoring oxygen uptake. The oxygen consumption test demonstrated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The oxygen consumption test demonstrated that a 0.02% GTC extract was much more effective against canola oil oxidation at 100°C than a 0.02% rosemary extract [109].…”
Section: Rapeseed Oilmentioning
confidence: 98%
“…The oxygen consumption test demonstrated that a 0.02% GTC extract was much more effective against canola oil oxidation at 100°C than a 0.02% rosemary extract [109].…”
Section: Rapeseed Oilmentioning
confidence: 98%
“…While jasmine tea, a flower-scented tea, is one of the most popular beverages consumed in China, to date there are only about ten references in the literature concerning the beneficial effects of drinking jasmine tea. [1,2,[9][10][11][12][13][14][15][16] Additionally, the difference in bioactivity between the base tea extract and the finished jasmine tea extract is still not clear.…”
Section: Introductionmentioning
confidence: 99%
“…2001). There were also reported that tea catechin reduces the formation of peroxides more effectively than α‐tocopherol, BHA in canola oil, porcine lard and chicken fat (Chen et al. 1998), food emulsion (Roedig Penman and Gordon 1997) and fish model system (He and Shahidi 1997).…”
Section: Introductionmentioning
confidence: 99%